Analysis on the electron density contour at different conditions over the equatorial region - Nagarajoo, K (2010)
In this paper, the contour of electron density (Ne) over the equatorial region were plotted using the (Ne) data from the International Ionosphere (IRI). The Ne data was taken on some dates in the years2003, 2004 and 2008. Then, the contour of Ne was analyzed in many different conditions such as in the context of different altitudinal heights, seasonal and diurnal varations, and at different sunspot numbers. Range of latitude from 3' to 10' and range of longitude from 100'110' were chosen to plot the contour. From the analysis done, it can be seen that the contour of Ne changes with variations in the altitude. In the context of different sunspot numbers, the Ne was highest in the year 2003 than year 2004 or 2008. As for the diurnal variation, the Ne over the equatorial region is unpredictable due to the formation of the ionosphere which varies diurnally. Through there is no seasonal variation over the equatorial region (i.e. Malaysia), the contour of Ne does show some difference in the contour plot two different months in the same year. From the contours of Ne and the analysis done at different conditions, the existence of ionospheric horizontal gradient over the equatorial region has been shown. Thus, by obtaining the contours of Ne over the equatorial region, the ionospheric horizontal gradient can be determined. Then, this ionospheric horizontal gradient can be utilized to determine the final GPS positioning improvement over the equatorial region.